Pengaruh advokasi pelayanan gizi dan penyuluhan terhadap jumlah kunjungan pasien di Poliklinik Gizi Rumah Sakit Umum Raden Mattaher Jambi - Mawarningsih Mawarningsih; Yayi Suryo Prabandari; R Dwi Budiningsari (Jurnal Gizi Klinik Indonesia, 2008)
Background: The number of patients’ visits at nutrition polyclinic is relatively low whereas the need of nutrition consultation at hospital polyclinic is high. Visits at nutrition polyclinic generally come from referrals of doctors at hospital polyclinics. The number of visits greatly depends on doctors referring patients to nutrition polyclinic. Low visit at nutrition polyclinic is due to the absence of socialization of nutrition service. It is necessary to conduct socialization of nutrition service by dissemination of information to outpatients and advocacy to stakeholders, especially doctors, who are expected to refer patients to nutrition polyclinic to increase visit.Objectives: To find out the effect of nutrition service advocacy and socialization to the number of visits at nutrition polyclinic of Raden Mattaher Hospital, Jambi.Methods: The study was a quasi-experimental using one group with pre-test and post-test design. Respondents of the study were doctors working in polyclinics and outpatients. There were 32 respondents of advocacy group and 180 respondents of socialization group. Data obtained were the number of patients’ visits analyzed statistically using Wilcoxon range test. Data of diagnostic types of patients having nutrition consultation were analyzed descriptively.Results: Advocacy of nutrition service to doctors and socialization to patients could increase visits of patients at nutrition polyclinic. There were significant increase of patients’ visits at nutrition polyclinic and visits based on diagnosis (p<0.05). A new type of diagnosis referred to nutrition polyclinic after intervention was found.Conclusion: Advocacy given to respondents who had made referral to nutrition polyclinic and socialization given to patients could increase the number of patients visiting nutrition polyclinic.